Pembelajaran Logika via Pendekatan Trilogi bagi Mahasiswa PAI yang Kritis dan Menyenangkan sebagai Generasi Z yang Aktif - Moh. Faizin; Kheisya Auliya Azzahroh; Lailatul Munawaroh; Irma Nur Setyani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The Trilogy of Sciences (Ontology, Epistemology, and Axiology) is a series of components that are inherent in the scope of Islamic Religious Education. This article aims to find out about Logic learning among PAI students as generation Z who are active, critical and not out of date. This writing uses the Library Research method, namely data processing using librarianship and literacy sources. Based on this, the conclusion of this article is that there are various kinds of foundations that can be used as buildings or basic foundations related to ontology, epistemology and axiology of Logic learning for PAI students to become an active, critical and fun Generation Z.